THE INFLUENCE OF CULTURE AND MOTIVATION TO DECISION ENTREPRENEURSHIP - Tarsisius Kana (Universitas Pendidikan Ganesha, 2017)
The Influence of Culture and Motivation to Decision Entrepreneurship (Studies in Student faculty of Economics and Business, Musamus University 2012 & 2013). The research aims to determine the influence of culture and motivation to decision enterpreneurship in students of the Faculty of Economics and Business, Musamus University 2012 & 2013. The sample of this research were 83 respondents drawn from each department management, accounting and economic development with the sampling method is purposive sampling. The analysis technique used is multiple linear regression.From the results of multiple linear regression analysis that has been processed in the obtained equation Y = 24,354 + 0,356 (X1) + 0,430 (X2) + e. From the result of testing the hypothesis that the T test and F test showed that the variables of culture and motivation influence and significant effect partially and significantly partially or simultaneously to the decision enterpreneurship to the students of the Faculty Economics and Business, University of Musamus Merauke force in 2012 and 2013. This is evidenced by the tvalue Culture (X1) 2.992 > ttable significant level of 1.6638 with 0.004 < 0.1 so that Ha accepted H0 is rejected. Motivation tvalue (X2) 4,704 > ttable 1.6638 with a significant level of 0.000 < 0.1 so that Ha accepted H0 is rejected. Then 21.186 Fcount> Ftable 3,11 with a significant level of 0.000 < 0.1 so that Ha accepted H0 is rejected. Value Adjusted R Square is 0.330, which means all of these variables together influence the decision amounted to 33%, while 67% are influenced by other variables not examined in the study.